Ragam Bahasa Nelayan di Adipala Cilacap : Kosakata Dan Pola Komunikasi Register (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study analyzes the linguistic varieties of the fishing community in Adipala, Cilacap, with a focus on distinctive vocabulary such as “bondo” (capital for sailing), “pancingan” (fishing gear), and “jaring lampara” (a type of fishing net). Employing a qualitative approach through observation, in-depth interviews, and document analysis, the research identifies lexical variations and register patterns used across different communicative contexts, including interactions among fishermen, fish trading transactions, and communication with the broader community. The findings reveal that fishermen’s registers serve not only as technical communication tools but also as markers of social and cultural identity and as a means of adaptation to technological and socio-economic changes. These results highlight the importance of preserving local fishermen’s vocabulary as part of cultural heritage and contribute to the development of sociolinguistic studies on professional groups in Indonesia. The study also recommends documentation and integration of local registers into education and community empowerment programs.